Beyond the Block: Sequential Spinal Anesthesia and Dexmedetomidine-Ketamine TIVA for a Four-Hour Cesarean Section in a 157-kg Parturient - Agung Nugroho; Ardana Tri Arianto; Paramita Putri Hapsari (Journal of Anesthesiology and Clinical Research, 2025)
Introduction: Cesarean delivery in super-obese parturients (BMI ≥ 50 kg/m²) presents a complex combination of anesthetic challenges, amplified by comorbidities like preeclampsia. The strong imperative to avoid airway instrumentation makes regional anesthesia the preferred technique. However, the finite duration of a single-shot spinal block poses a significant risk in unexpectedly prolonged procedures, requiring a pre-planned strategy for anesthetic extension. Case presentation: A 38-year-old G2P1 parturient with a BMI of 63.7 kg/m² presented for an emergency cesarean section for fetal hypoxia and preeclampsia. After a rapid multidisciplinary consultation, a deliberate decision was made to proceed with spinal anesthesia to mitigate profound airway risks. The surgery became unexpectedly complex, lasting four hours. As the spinal block regressed, a planned transition to an opioid-sparing total intravenous anesthesia (TIVA) with dexmedetomidine and ketamine was initiated. This technique preserved spontaneous respiration and provided excellent hemodynamic stability, even during a 2000 mL hemorrhage. Conclusion: This case highlights the value of anesthetic adaptability in high-risk obstetrics. A sequential spinal-TIVA technique offers a safe and effective alternative to a high-risk conversion to general anesthesia, emphasizing the importance of having a pre-planned contingency for insufficient neuraxial blockade in super-obese parturients. This approach underscores the necessity of multidisciplinary communication and patient-centered care in navigating complex obstetric emergencies.